Legal Aspects of Digital Proof in Medical Criminal Cases in Healthcare Services in Hospitals - Kembaren, Novalina Br; Simarmata, Marice; Zarzani, Riza (PT FORMOSA CENDEKIA GLOBAL, 2025)
The legal force of electronic evidence in criminal proof in Indonesia, recognized through the ITE Law but creating interpretive challenges due to disharmony with the KUHAP. Although the UU ITE expands the definition of evidence, authentication and collection validity requirements are not yet unified. The Constitutional Court decision and the amendment to the ITE Law provide clarification, particularly regarding wiretapping. In the context of medical criminal cases in hospitals, electronic medical records (EMR) are important but are hampered by the limitations of the KUHAP. Legal uncertainty regarding the submission, verification, and assessment of electronic evidence in medical criminal cases highlights the urgency of revising the KUHAP to comprehensively accommodate electronic evidence for the sake of legal certainty and justice.